IMPLEMENTASI STRUKTUR CERITA ARCHPLOT PADA FILM ANIMASI HYBRID BERJUDUL BHUMI - SURASA SURASA; SEKAR KHAIRUNNISA ARUM MEIDINASARI (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2022)
The structure of the storyline archplot is a storyline that has a goal orientation where the occurrence of a good or bad event that makes a character's life change, encourages the desire of the character to struggle consciously or unconsciously to restore his life as before. Characters will be encouraged to undergo a missionary journey based on their desire to fight the forces of antagonism (inner, personal, extra-personal). Characters may or may not achieve their goals. Archplot has the characteristics of 3 acts, 6 stages and 5 turning points. These three rounds consist of beginning/Set-Up (act 1), middle confrontation (act 2), end resolution (act 3). While the six parts consist of Set-Up, new situation, progress, complications & higher stakes, final push, and aftermath. Then, the turning point of the story consists of opportunity, change of plans, point of no return, major setback and climax. The animated film “BHUMI” was made using hybrid animation techniques. This technique is a combination of two-dimensional and three-dimensional animation media. ABSTRAKmerupakan alur cerita yang mempunyai orientasi tujuan dimana terjadinya suatu peristiwa baik atau buruk yang membuat kehidupan karakter berubah, mendorong keinginan dari karakter untuk berjuang secara sadar maupun tidak sadar untuk mengembalikan kehidupannya seperti semula. Karakter akan didorong untuk menjalani suatu perjalanan misi didasari keinginannya melawan kekuatan antagonisme (inner, personal, extra-personal). Karakter bisa atau tidak bisa mencapai tujuannya. Archplot mempunyai ciri-ciri terdapat 3 babak (acts), 6 bagian (stages) dan 5 titik balik cerita (turning points). Ketiga babak ini terdiri dari beginning/Set-Up (act 1), middle confrontation (act 2), end resolution (act 3). Sedangkan keenam bagian terdiri dari Set-Up, new situation, progress, complications & higher stakes, final push, dan aftermath. Lalu, titik balik cerita terdiri dari opportunity, change of plans, point of no return, major setback dan climax. Film animasi “BHUMI” ini dibuat dengan teknik animasi hybrid. Teknik ini merupakan kombinasi media animasi dua dimensi dan tiga dimensi.